Dichlorido{N,N-dimethyl-N `-[1-(2-pyridyl)ethylidene]ethane-1,2-diamine-kappa N-3,N `,N `'}copper(II) - Salga, M.S.; Khaledi, H.; Ali, H.M.; Puteh, R. (International Union of Crystallography, 2010)
In the title compound, [CuCl2(C11H17N3)], the Cu-II ion is five-coordinated with a distorted square-pyramidal configuration. The three N atoms of the Schiff base ligand and one Cl atom are located in the basal plane, whereas the other Cl atom is apically positioned.